LOCAL SAMOSIR ONION (Allium Ascalonicum L.) CULTIVATION POTENTIAL: POTENSI BUDIDAYA BAWANG MERAH (Allium Ascalonicum L.) LOKAL SAMOSIR - Mintodeus waruwu, Marinus (UPMI Proceeding Series, 2023)
Shallots (Allium ascalonicum L.) is one of the vegetable commodities that is widely used by the community as a flavoring ingredient. Samosir Regency is known as a shallot producing area in North Sumatra, but the golden age of shallots has faded even farmers who still survive in shallots can be counted on fingers. The growing demand for shallots is not offset by onion production. The purpose of this study was to see the production of shallots through the induction of gamma-ray radiation mutations and the concentration of ZPT administration and soaking duration. The data used in this study were secondary data from different sources. The results of gamma ray radiation show that gamma ray irradiation with doses of 1, 2, 3, 4, 5 Gy produces 11 plant individuals with the highest score that have the potential to produce plants with good growth character. ZPT concentration and soaking duration have a noticeable effect on the number of tubers. The interaction of coconut water concentration with soaking duration had no real effect on all observation parameters.